Over the line - Lloyd, David T., 1954- (Syracuse University Press, 2013)
This book is a coming of age tale about a boy's emotional growth and a set of crises that must be addressed and overcome. This novel explores stresses and fractures in contemporary life in a fictional small town in upstate New York.